2016
DOI: 10.4244/eijy15m05_02
|View full text |Cite
|
Sign up to set email alerts
|

COmplex coronary Bifurcation lesions: RAndomized comparison of a strategy using a dedicated self-expanding biolimus-eluting stent versus a culotte strategy using everolimus-eluting stents: primary results of the COBRA trial

Abstract: As compared with a culotte strategy with XIENCE stents, complex bifurcation stenting using a dedicated strategy combining Axxess and BioMatrix stents results in similar stent strut coverage at nine-month follow-up, and a significantly larger lumen and lower angiographic late lumen loss in the proximal MV.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 30 publications
0
22
0
Order By: Relevance
“…In this trial, the Tryton SB stent in combination with a MV DES was compared with SB balloon angioplasty in combination with a main branch DES only (provisional strategy), indicating a less complex subset of bifurcation lesions where provisional stenting was deemed a possible treatment option up‐front. The patient population therefore differs significantly from this (COBRA) study where the patients had long lesions in large caliber coronary bifurcations , and can therefore be considered as complex and true bifurcation lesions where a two‐stent strategy was deemed necessary from the outset.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…In this trial, the Tryton SB stent in combination with a MV DES was compared with SB balloon angioplasty in combination with a main branch DES only (provisional strategy), indicating a less complex subset of bifurcation lesions where provisional stenting was deemed a possible treatment option up‐front. The patient population therefore differs significantly from this (COBRA) study where the patients had long lesions in large caliber coronary bifurcations , and can therefore be considered as complex and true bifurcation lesions where a two‐stent strategy was deemed necessary from the outset.…”
Section: Discussionmentioning
confidence: 95%
“…The design of the COBRA study has been reported previously . Briefly, the study is a prospective randomized controlled two‐center trial (http://ClinicalTrials.gov NCT01486095), comparing a dual stenting culotte approach with two everolimus‐eluting Xience PRIME stents (Abbott Vascular, Santa Clara, CA), widely accepted as one of the preferred two‐stent bifurcation techniques, with a strategy using Axxess, a dedicated self‐expanding conical biolimus‐eluting bifurcation system and additional biolimus‐eluting Biomatrix stents in branches (Biosensors Europe SA, Morges, Switzerland).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The overall complication rate was low, with a single access site-related retroperitoneal bleed, and a single coronary perforation following post dilatation of the MV AXXESS stent, representing a 2 % complication rate, 12 similar to that in other published series. 16 The single randomised trial in the literature, the COBRA study, 18 compares the use of the AXXESS system alongside Biomatrix stents with a two-stent culotte strategy using Xience Pro stents (Abbott Vascular, Illinois, USA) in a cohort of 40 patients with true bifurcation lesions. The trial was conducted at two European centres, with FKB inflations being performed in all cases.…”
Section: Discussionmentioning
confidence: 99%
“…The Biolimus-eluting Axxess TM bifurcation device (Biosensors International, Morges, Switzerland) is the only second generation drug-eluting dedicated bifurcation stent currently on the market with sufficient clinical data available confirming its safety and efficacy in the treatment of complex coronary bifurcation lesions [13][14][15]. Moreover, the recent COBRA study found that as compared with a culotte strategy with the Xience everolimus-eluting metallic stents (Abbott Vascular, Santa Clara, California), complex coronary bifurcation lesion stenting using a dedicated strategy combining the Axxess and Biomatrix biolimuseluting metallic stents resulted in similar stent strut coverage at 9 months follow-up, but a significantly larger lumen in the proximal main vessel (MV) [16].…”
Section: Rationale For Bifurcation Techniques Assessedmentioning
confidence: 99%